314. Discordant Microbiology Cultures From Paired Osteomyelitis Bone Specimens Should Question the Current Approach to Evaluation. (26th November 2018) - Barshes, Neal; Trautner, Barbara W; Mindru, Cezarina; Rodriguez-Barradas, Maria
Abstract: Background: Published foot osteomyelitis series typically report treatment failure rates of 20% or more. The role of persistent vs. new infections in this treatment failure is unclear. Methods: We identified treatment failure among all cases of probable or definite osteomyelitis at a single Houston hospital between 2011 and 2016. Treatment typically consisted of surgical resection of grossly affected bone and 2–12 weeks of antibiotic therapy selected based on bone culture results. Treatment failure was defined as either: (1) unplanned resection of additional bone contiguous the previous area of treatment; or (2) leg (above-ankle) amputation. Cases were included if paired bone cultures (initial operation + reoperation for treatment failure) were obtained. Cohen's kappa was calculated to estimate concordance between isolates seen at the initial Results: 208 cases of definite or probable osteomyelitis were reviewed. Treatment failure occurred in 55 cases (26%), 35 of which had microbiology results from paired bone specimens. Initial cultures identified 70 bacterial and 1 fungal isolates, repeat cultures identified 77 bacterial and 3 fungal isolates. Overall concordance was poor (kappa = 0.180). Species and group-specific concordance ranged from poor to moderate (see table). Staphylococcus aureus, nonpseudomonal Gram-negative aerobes, and anaerobes were the most common discordant bacteria to be seen at reoperation for treatment failure. Enterococcus appeared to be the most persistent organism, i.e., most commonly seen in both specimens. Conclusion: Microbial isolates identified by conventional cultures at the time of reoperations for treatment failure differ significantly from those seen at the initial operation. Better diagnostic methods may help in understanding the degree the role of persistent unidentified microbes vs. new microbes in treatment failure. Disclosures: B. W. Trautner, Paratek: Consultant, Consulting fee Zambon: Consultant, Consulting fee and Research grant